2012
DOI: 10.4013/ete.2011.72.03
|View full text |Cite
|
Sign up to set email alerts
|

Conventional concrete with addition of recycled rubber tires: Study of the mechanical properties

Abstract: Resumo AbstractO mundo vive hoje a necessidade premente da diminuição de emissão de gases de efeito estufa, da diminuição e se possível da nulidade de descartes e despejo de materiais resultantes de processos produtivos que poluem e degradam o meio ambiente.Dentre esses problemas os pneus inservíveis tem se tornado um grande problema para meio ambiente devido a anos de disposições incorretas. No movimento de reaproveitamento, reciclagem e eliminação de resíduos, o setor da construção civil tem se tornado um gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Higher to providing adequate structure life at a cost competitive with other materials, it enables the large-scale use of potentially environmentally polluting wastes from other industrial processes (Tutikian, Isaia, & Helene, 2011). Several authors have studied and confirmed the feasibility of using fragmented rubber in addition or substitution of natural aggregate in concrete (Ferreira, Gachet-Barbosa, Cecche Lintz, Russo Seydell, & Jaquiê Ribeiro, 2013;Issa & Salem, 2013;Ling, 2012;Lintz, Barbosa, Seydell, & Jacintho, 2010;Pelisser, Zavarise, Longo, & Bernardin, 2011;Shen et al, 2013;Verzegnassi, Lintz, Barbosa, & Jacintho, 2012). One of the properties of rubber concrete is greater ductility, i.e., rubber concrete provides greater deformation capacity before rupture.…”
Section: Application Of Unserviceable Tiresmentioning
confidence: 98%
“…Higher to providing adequate structure life at a cost competitive with other materials, it enables the large-scale use of potentially environmentally polluting wastes from other industrial processes (Tutikian, Isaia, & Helene, 2011). Several authors have studied and confirmed the feasibility of using fragmented rubber in addition or substitution of natural aggregate in concrete (Ferreira, Gachet-Barbosa, Cecche Lintz, Russo Seydell, & Jaquiê Ribeiro, 2013;Issa & Salem, 2013;Ling, 2012;Lintz, Barbosa, Seydell, & Jacintho, 2010;Pelisser, Zavarise, Longo, & Bernardin, 2011;Shen et al, 2013;Verzegnassi, Lintz, Barbosa, & Jacintho, 2012). One of the properties of rubber concrete is greater ductility, i.e., rubber concrete provides greater deformation capacity before rupture.…”
Section: Application Of Unserviceable Tiresmentioning
confidence: 98%